Electrical behaviour of nanosilver doped gallium flexible conductor for biomedical application - Shan, Kho Y.; Mahmood, Anwar; Islam, Sumaiya; Debnath, Sujan; Mas Ayu, Hassan (IOP Publishing, 2019)
In the biomedical field, continuous researches have been expanding on doping of metals to acquire new materials for flexible conductors. Flexible conductors have been rapidly sought in several biomedical applications such as biosensors, implants, prostheses, etc. For example, prostheses are to mimic the movement of the human body which enables flexible and repetitive movement. However, these alloys functions hampered due to fatigue or loss of conductivity when subjected to bending. To address such issue, gallium is a potential solution as it has high ductility. However, gallium has relatively low electrical conductivity. In order to enhance the conductivity, nanosilver was used to doped as silver has the highest electrical conductivity. Moroever, nanosilver enables better diffusibility into the gallium matrix. In this research, for doping process, gallium and nanosilver were mixed at six different ratios, which were Ga:Ag of 1:1, 2:1, 3:1, 4:1, 5:1 and 6:1. It is revealed that higher concentration of gallium to nanosilver provides better diffusion, and better electrical behaviour. It is also revealed that the Ga:Ag of 3:1 is the most effective concentration in terms of better homogeneity and lower electrical resistance. Such findings are crucial for proper doping process and considered as the founding parameters for better alloy formation. Nevertheless, these findings would also contribute to biomedical research industry especially for artificial organ through developing new alloy materials.